2014
DOI: 10.1083/jcb.201407082
|View full text |Cite
|
Sign up to set email alerts
|

STIM1- and Orai1-mediated Ca2+ oscillation orchestrates invadopodium formation and melanoma invasion

Abstract: Calcium signaling mediated by STIM1 and Orai1 activates Src to promote invadopodium assembly while simultaneously promoting MT1-MMP recycling to the plasma membrane to promote ECM degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
186
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(198 citation statements)
references
References 59 publications
8
186
0
4
Order By: Relevance
“…The contractile force that moves the cell body is then transmited to focal adhesions by phospho-myosin II-based actomyosin contraction. This phosphorylation was abolished by In addition to focal adhesions, podosomes and invadopodia are also adhesion structures regulated by Ca oscillations, which promote invadopodia formation and extracellular matrix (ECM) degradation [65]. These authors found that Ca entry with thapsigargin or ionophore A23187 led to the same result, i.e., a rapid increase of pY416 Src levels.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The contractile force that moves the cell body is then transmited to focal adhesions by phospho-myosin II-based actomyosin contraction. This phosphorylation was abolished by In addition to focal adhesions, podosomes and invadopodia are also adhesion structures regulated by Ca oscillations, which promote invadopodia formation and extracellular matrix (ECM) degradation [65]. These authors found that Ca entry with thapsigargin or ionophore A23187 led to the same result, i.e., a rapid increase of pY416 Src levels.…”
supporting
confidence: 69%
“…, or the inhibition of SOCE with 2-APB, reduced pY416 Src levels, strongly suggesting a direct role of STIM1-ORAI1-mediated Ca 2+ inlux in the preservation of Src activity and invadopodia formation [65].…”
mentioning
confidence: 99%
“…Using knockdown strategies, the authors demonstrated that both Orai1 and STIM1 are critical for mediating invadopodium formation and its proteolytic activity (98). Suppression of SOCE abrogated recruitment of matrix metalloproteinase (MT1-MMP) to the plasma membrane (98). Further, microarray analysis on melanoma tissues showed higher STIM1 and Orai1 expression in metastatic tissues compared with benign samples (98).…”
Section: Melanomamentioning
confidence: 99%
“…Sun et al (98) reported that Ca 2ϩ oscillations as a consequence of SOCE are required for invadopodium formation and extracellular matrix (ECM) degradation. Using knockdown strategies, the authors demonstrated that both Orai1 and STIM1 are critical for mediating invadopodium formation and its proteolytic activity (98). Suppression of SOCE abrogated recruitment of matrix metalloproteinase (MT1-MMP) to the plasma membrane (98).…”
Section: Melanomamentioning
confidence: 99%
“…Our previous results show that β 2 AR activation drives a cAMPCa 2+ signaling loop in cancer cells that contributes to cell invasion . As a ubiquitous second messenger, Ca 2+ is implicated in many intracellular processes including actin remodeling (Li et al, 2001;Wang et al, 2010), force generation (Bers, 2000), motility (Clapham, 2007), invadopodia formation (Sun et al, 2014) and tumor progression (Monteith et al, 2012). To determine the extent to which the increased Ca 2+ levels induced by βAR activation were associated with cell deformability, we chelated cytosolic Ca 2+ using the cell-permeable Ca 2+ chelator, BAPTA-AM; we then investigated the effect of isoproterenol on cell retention with PMF and on invasive behavior with the 3D scratch wound invasion assay.…”
Section: βAr Activation Increases F-actin Levelsmentioning
confidence: 99%